Bis(aminoaryl) Carbon‐Bridged Oligo(phenylenevinylene)s Expand the Limits of Electronic Couplings. (1st February 2017) - Burrezo, Paula Mayorga; Lin, Nai‐Ti; Nakabayashi, Koji; Ohkoshi, Shin‐ichi; Calzado, Eva M.; Boj, Pedro G.; Díaz García, María A.; Franco, Carlos; Rovira, Concepciò; Veciana, Jaume; Moos, Michael; Lambert, Christoph; et al.
Abstract: Carbon‐bridged bis(aminoaryl) oligo( para ‐phenylenevinylene)s have been prepared and their optical, electrochemical, and structural properties analyzed. Their radical cations are class III and class II mixed‐valence systems, depending on the molecular size, and they show electronic couplings which are among the largest for the self‐exchange reaction of purely organic molecules. In their dication states, the antiferromagnetic coupling is progressively tuned with size from quinoidal closed‐shell to open‐shell biradicals. The data prove that the electronic coupling in the radical cations and the singlet–triplet gap in the dications show similar small attenuation factors, thus allowing charge/spin transfer over rather large distances.